Ketamine and Norketamine: Enantioresolution and Enantioselective Aquatic Ecotoxicity Studies. (10th March 2021) - Pérez‐Pereira, Ariana; Ribeiro, Cláudia; Teles, Filomena; Gonçalves, Ricardo; M.F. Gonçalves, Virgínia; Pereira, José Augusto; Carrola, João Soares; Pires, Carlos; Tiritan, Maria Elizabeth
Abstract: Ketamine is a chiral drug used for various clinical purposes but often misused. It is metabolized to norketamine, an active chiral metabolite. Both substances have been detected in environmental matrices, but studies about their enantioselective toxic effects are scarce. In the present study, the enantiomers of ketamine and norketamine were separated by a semipreparative enantioselective liquid chromatography method, and their toxicity was investigated in different aquatic organisms. The enantioseparation was achieved using a homemade semipreparative chiral column. Optimized conditions allowed the recovery of compounds with enantiomeric purity higher than 99%, except for ( R )‐ketamine (97%). The absolute configuration of the enantiomers was achieved by experimental electronic circular dichroism (ECD). The ecotoxicity assays were performed with the microcrustacean Daphnia magna and the protozoan Tetrahymena thermophila using Toxkit MicroBioTests. Different concentrations were tested (0.1–10 000 µg/L) to include environmental levels (~0.5–~100 µg/L), for racemates ( R, S ) and the isolated enantiomers ( R or S ) of ketamine and norketamine. No toxicity was observed in either organism at environmental levels. However, at greater concentrations, ( R, S )‐ketamine presented higher mortality for D. magna compared with its metabolite ( R, S )‐norketamine (85 and 20%, respectively), and the ( S )‐ketamine enantiomer showed higher toxicity than the ( R )‐ketamine enantiomer. In addition, ( S )‐ketamine also presented higher growth inhibition than ( R )‐ketamine for T. thermophila at the highest concentrations (5000 and 10 000 µg/L). Contrary to D. magna, growth inhibition was observed for both enantiomers of norketamine and in the same magnitude order of the ( S )‐ketamine enantiomer. The results showed that the 2 organisms had different susceptibilities to norketamine and that the toxicity of ketamine at high concentrations is enantioselective for both organisms. Environ Toxicol Chem 2022;41:569–579. © 2020 SETAC